Manufacturers response to climate change - Rattanakit, Rattanachai (Cranfield University, 2007)
There is now clear scientific proof which indicates that emissions from economic activity, particularly the industrial sector, are the main cause of the change in global climatic conditions. The Stern Review describes climate change as the greatest market failure the world has ever seen. UK alone contributes more than 6.5 billion tonnes of the global carbon dioxide emissions every year. This, along with other scientific evidence, has led the UK government to publish Climate Change Bill that aims to reduce the UK overall emissions of greenhouse gases, mainly carbon dioxide, by 60% as early as 2060. The government understands the importance of the set targets and recognises that it will require collaboration from both business and individuals. Credible strategies together with determined implementation will be needed if the set targets are to be met within the timescale. This study analysed manufacturing and related companies and found that many companies have already acknowledged the climate change issue and, seemingly, have begun to tackle it by reducing energy demand through various initiatives. However, evidence of true low-carbon manufacturing companies is not seen and, therefore, this led the research to further investigate and seek for good practices. This study is intended to provide an analysis of compiled strategies learned from different manufacturing sectors in the UK. In addition, the project used a steps-to-change model to provide a wider view of how far the participating manufacturers have gone in responding to climate change. Furthermore, it provides recommendations of how the government can act to help accelerate and encourage UK companies to do much more to help tackle climate change.